Watch out for the Robot! Designing Visual Feedback Safety Techniques When Interacting With Encountered-Type Haptic Displays - Mercado, Victor Rodrigo; Argelaguet, Ferran; Casiez, Gery; Lécuyer, Anatole (Frontiers in Virtual Reality, 2022)
Encountered-Type Haptic Displays (ETHDs) enable users to touch virtual surfaces by using robotic actuators capable of co-locating real and virtual surfaces without encumbering users with actuators. One of the main challenges of ETHDs is to ensure that the robotic actuators do not interfere with the VR experience by avoiding unexpected collisions with users. This paper presents a design space for safety techniques using visual feedback to make users aware of the robot's state and thus reduce unintended potential collisions. The blocks that compose this design space focus on what and when the feedback is displayed and how it protects the user. Using this design space, a set of 18 techniques was developed exploring variations of the three dimensions. An evaluation questionnaire focusing on immersion and perceived safety was designed and evaluated by a group of experts, which was used to provide a first assessment of the proposed techniques.